Análise de atos de concentração econômica e de condutas anticompetitivas no mercado de cimento no Brasil - Silva, Eduardo Polini Marinho da (Universidade Federal de São Carlos, 2025)
Cement is a widely used material and holds significant importance and impact in the construction sector in Brazil and many other countries. The cement market is characterized by relevant concentration within a small number of economic groups (Cunha; Fernandez, 2003; Dornelas, 2013; Santos, 2011), which, according to theory, increases the likelihood of the exercise of market power (Church; Ware, 2000). In this context, the present study aims to analyze economic concentration acts and anticompetitive practices judged by the Administrative Council for Economic Defense (Cade) between 2015 and 2023. Regarding the reviewed concentration acts, it was observed that most were approved without restrictions, and the majority were also processed under a fast–track procedure. As for anticompetitive practices, all the administrative proceedings were dismissed. Thus, although there were economic concentration operations, it was found that they did not harm competition. Furthermore, the administrative proceedings concerning alleged anticompetitive practices judged during the study period were also dismissed.
Analysis of merges and anticompetitive conduct in the cement market in Brazil
Keywords: Mercado de Cimento; Concentração; Condutas; Anticompetitivas; Market of Cement; Concentration; Anticompetitive; Conducts; CIENCIAS SOCIAIS APLICADAS::ECONOMIA